(untitled) (GESTIÓN Y TENDENCIAS, 2019)
In emerging economies, as some Latin American economies are, governments make efforts to increase firms’ innovation in order to raise society’s welfare. The expected objectives, however, are often not met. This is partly the result of the presence of informal firms, which discourage innovation among formal ones.